2014
DOI: 10.3390/toxins6113117
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sterigmatocystin Concentrations in Urine for Monitoring the Contamination of Cattle Feed

Abstract: This study aimed (1) at determining the levels of the fungal toxin sterigmatocystin (STC) in the feed and urine of cattle and (2) at evaluating the effects of supplementing the feed with a mycotoxin adsorbent (MA) on STC concentrations in urine. Two herds of female Japanese Black cattle were used in this study. The cattle in each herd were fed a standard ration containing rice straw from different sources and a standard concentrate; two groups of cattle from each herd (n = six per group) received the commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Fushimi (Fushimi et al, 2014) investigated STC in urine only. Fushimi (Fushimi et al, 2014) investigated STC in urine only.…”
Section: Enniatins Beauvericin Sterigmatocystinmentioning
confidence: 99%
“…Fushimi (Fushimi et al, 2014) investigated STC in urine only. Fushimi (Fushimi et al, 2014) investigated STC in urine only.…”
Section: Enniatins Beauvericin Sterigmatocystinmentioning
confidence: 99%
“…In vivo studies have revealed an extensive metabolization of STERIG, consequently free STERIG was scarcely detected in the urine of animals (Fushimi et al., ). Fushimi et al.…”
Section: Sterigmatocystinmentioning
confidence: 99%
“…All urine samples were analysed using LC‐MS/MS according to our previous study (Fushimi et al., ; Takagi et al., ). Briefly, 0.5 ml of a urine sample was mixed with 3.0 ml of 50 m m ammonium acetate buffer (pH 4.8) and 10 μl of glucuronidase/arylsulfatase solution and incubated for 12 hr at 38°C.…”
Section: Methodsmentioning
confidence: 99%
“…Creatinine concentrations in the urine were determined using a commercial kit, the Sikarikit‐S CRE (Kanto Chemical, Tokyo, Japan) following the manufacturer's instructions, and measured using the BM8060 Clinical Analyzer (Nihon‐Denshi, Tokyo, Japan). The urinary concentrations of ZEN, α‐ZOL, β‐ZOL and STC were expressed as a ratio to creatinine (pg/mg Crea), as described previously (Fushimi et al., ; Takagi et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation